Nonlinear analysis of operator electroencephalograms subjected by electromagnetic noise radiation - A. V. Sidorenko; N. A. Solodyho (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The experimental investigation of operator electroencephalograms subjected by electromagnetic noise radiation is described. Using the nonlinear methods (Higuchi method and Wolf method) with the preliminary noise suppression by the wavelet transformation with base Haar and Dobeshi 4 functions) makes is possible to characterize structural variations of the analyzed electroencephalograms subjected to the electromagnetic noise waves by the fractal dimension and the first Lyapunov exponents. As shown the fractal dimension was increasing more than 9,6 and 10,0 % accordingly in comparative this parameter without the preliminary processing of analyzing electroencephalograms without electromagnetic noise. It is noted the increasing of fractal dimension to 1,6 and 7,3 % subjected to the electromagnetic noise and used preliminary processing of electroencephalograms by the wavelet transformation with base Haar and Dobeshi 4 functions relatively noise action without preliminary processing electroencephalograms. Using Wolf method with the preliminary noise suppression by the wavelet transformation is possible to reveal the change the sign from positive to negative. It is obviously, that preliminary processing of electroencephalograms is lead to stability of function the brain of operator.